Mental health literacy in patients with acute myocardial infarction: a cross-sectional registry-based study - Kirchberger, Inge; Fischer, Simone; Raake, Philip; Linseisen, Jakob; Meisinger, Christine; Schmitz, Timo (Frontiers in Psychiatry, 2024)
IntroductionThis study aimed to explore mental health literacy (MHL) and its related factors in a cross-sectional, registry-based sample of patients after acute myocardial infarction (AMI).MethodsAll survivors of AMI between 2017 and 2019 from the Myocardial Infarction Registry Augsburg (n=1.712) received a postal questionnaire on MHL (Mental Health Literacy Scale (MHLS-GER)) and single questions on experiences with and information on mental disorders in 2023. The response rate was 49.9%. Logistic and linear regression models were used to investigate the associations between these variables and sociodemographic factors.ResultsIn the sample of 855 patients (77.5% male, mean age 71.4 ± 10.9 years), 30.0% had experienced mental problems about 5 years after AMI. Among these, 17.4% received psychotherapy and 26.1% psychotropic drugs. Information about possible mental problems after their AMI was obtained from a physician by 30.8% of the patients and in a rehabilitation setting by 46.4%, respectively. Of the patients, 26.2% wished to receive more information on mental problems after AMI. MHLS-GER subscale scores ranged between and 54 (“Social distance”) and 76 (“Information seeking”) (best score 100). Age was the most important factor that was significantly associated with the report of mental health problems, a perceived lack of information, help seeking behavior and treatment, and MHL.DiscussionElderly and poorly educated patients were at risk of poor MHL. Further studies are required to specify the role of MHL in post-AMI life and health care.